Given:
P(x) is a 2nd degree polynomial.
[tex]P(1)=0,\ P(2)=3,\ P(-3)=0[/tex]
To find:
The polynomial P(x).
Solution:
If P(x) is a polynomial and P(c)=0, then c is a zero of the polynomial and (x-c) is a factor of polynomial P(x).
We have, [tex]P(1)=0,\ P(-3)=0[/tex]. It means 1 and -3 are two zeros of the polynomial P(x) and (x-1) and (x+3) are two factors of the polynomial P(x).
So, the required polynomial is defined as:
[tex]P(x)=a(x-1)(x+3)[/tex] ...(i)
Where, a is a constant.
We have, [tex]P(2)=3[/tex]. So, substituting [tex]x=2,\ P(x)=3[/tex] in (i), we get
[tex]3=a(2-1)(2+3)[/tex]
[tex]3=a(1)(5)[/tex]
[tex]3=5a[/tex]
[tex]\dfrac{3}{5}=a[/tex]
Putting [tex]a=\dfrac{3}{5}[/tex] in (i), we get
[tex]P(x)=\dfrac{3}{5}(x-1)(x+3)[/tex]
Therefore, the required polynomial is [tex]P(x)=\dfrac{3}{5}(x-1)(x+3)[/tex].